(untitled) (Indian Journal of Animal Production and Management, 2014)
The present study was carried out to characterize the Rajapalayam dog breed. Due to the delightful appearance and hardy nature, the Rajapalayam breed of dogs is more familiar among the pet owners and breeders as guarding dogs. This breed of dog having its breeding tract at Rajapalayam Taluk of Virudhunagar district in Tamil Nadu, India. Rajapalayam dogs of different age groups maintained under normal domestic management environment by different families were randomly selected and identified for recording the physical measurements of dog.By the current study, Rajapalayam dog breed is a hound dog and falls in the mid sized hound dog category. The average body weight of Rajapalayam dog ranges from 25-30 kg and the height falls within the range of 65 to 72 cm.